Experimental evidence for the formation mechanism of metallic catalyst-free carbon nanotubes - Tang, Y. H.; Li, X. C.; Li, J. L.; Lin, L. W.; Xu, H. F.; Huang, B. Y. (Nano-Micro Letters, 2010)
Our work reported that the so-called pure carbon nanotubes (CNTs) can be synthesized without metallic catalyst by chemical vapor deposition (CVD). The as-prepared CNTs have average diameter of 50 nm and length over several microns. Analysis of intermediate objects in the products indicates that their formation mechanism follows the wire-to-tube model. Besides, according to thermodynamic analysis of the driving force combing with experimental results, we find that the thermal gradient can effectively favor the formation of CNTs in our metallic catalyst-free CVD.